A review on the ethnopharmacology, metabolites, pharmacological uses, and toxicology of Ficus hirta (Moraceae) Vahl - Minghui Chen; Jiao Liu; Sihua Zou; Jingquan Yuan; Jiyu Pan; Zhenmei Lin; Yanchun Wu; Yanchun Wu; Bei Zhou; Bei Zhou (Frontiers in Pharmacology)
Ficus hirta Vahl, a member of the Moraceae family and genus Ficus, is a traditional medicinal plant with diverse metabolites. Traditionally, Ficus hirta Vahl has been used in Asian countries to treat various ailments including indigestion, loss of appetite, cold, pneumonia, tuberculosis, cough, asthma, excessive sweating, backache, bruises, arthritis, liver diseases, skin conditions, gynecological disorders, and pediatric illnesses. As a botanical drug with both medicinal and nutritional applications, Ficus hirta Vahl is an integral part of China’s multi-ethnic medical system, serving as a tonic for many years. Approximately 130 chemical metabolites have been identified from Ficus hirta Vahl to date, including flavonoids, phenylpropanoids, phenolics, phenol glycosides, terpenoids, sterols, quinones, and esters. The bioactive properties of Ficus hirta Vahl extracts include immune modulation, enhancement of digestive system function, antitussive and antiasthmatic effects, as well as antibacterial, anti-inflammatory, antioxidant, anti-aging, hepatoprotective, anti-radiation, and antitumor activities. Toxicological assessments confirmed the safety and nontoxicity of Ficus hirta Vahl A thorough review of the literature underscores the significant potential of Ficus hirta Vahl across multiple domains such as medicine, food, and agriculture. However, research on Ficus hirta Vahl remains limited, necessitating further investigation into its pharmacokinetics and mechanisms of action.